Migración de la plataforma de red y almacenamiento a un sistema virtualizado en la empresa Maint S.A. - Lara Herrera, Luis Miguel (2017)
The management and control of IT resources is important for the entire organization because it helps the company to have a better technological growth, where the architectural model of its infrastructure is sustainable for future changes. For the preparation of the present work, we analyzed the current situation with the aim of identifying the most representative problems and possible predictive failures that results occur at the center of the data is not restructured a server level. In order to propose a reliable design for the management of information according to the recommendations issued by the software manufacturer for virtualized systems. In this work titling establishes the new design for the operation of the servers MAINT SA operates as a virtualized environment, offering a high availability of services that provides both internal and external agents of the entity, as well as the virtualization of the Integrity In the management of information with a distributed system of services and managed through a reliable storage network. After performing a survey of an operational technological level of the data center, a design was done where all the equipment was analyzed to define which are compatible with the virtualization tool and also to know which are the scalable equipment with future technologies. Finally, a cluster with two servers was configured and all the virtual machines were migrated on them by means of a centralized console for the virtual management, the four paths between servers and the storage was designed in a redundant way by means of a SAN configuration.